The Development of LearningApps.org-Based Learning Media for Vocabulary Introduction on the Theme Schule for Grade XI Students of SMAN 1 Menganti - Putra, Jordan Yuseno; Titaley, Audrey Gabriella (LATERNE, 2025)
This research was based on interviews and classroom observations conducted during the PLP (Teaching Practicum) at SMAN 1 Menganti, which revealed that students rarely utilized digital media such as LearningApps.org in German language lessons. In response to this situation, this research aimed to explore the integration of digital media, particularly for introducing German vocabulary. Based on these findings, the development of instructional media was considered necessary to support students' vocabulary acquisition and preparatory language practice. The objective of this research was to develop instructional media using LearningApps.org, focusing on the Gruppenzuordnung (grouping) activity format. The thematic content was adapted to the material used in Grade XI German classes at SMAN 1 Menganti, specifically the theme Schule. In addition, this study aimed to obtain expert assessments to determine the appropriateness and quality of the developed media. The development process followed the ADDIE model proposed by Branch (2009), which includes five stages: analysis, design, development, implementation, and evaluation. However, this study was limited to the third stage—development, as its purpose was to assess the feasibility of the instructional media only. The data were collected by distributing validation forms to media and content experts. The experts’ responses were then analyzed using a Likert scale-based feasibility formula. The results showed that the media received a feasibility rating of 95.71% from the content expert and 92% from the media expert, placing it in the category of highly feasible and indicating no revisions were necessary. Based on these findings, it can be concluded that the instructional media using LearningApps.org with the theme Schule was successfully developed and validated in terms of both content and media design.